Potensi buah zanthoxylum acanthopodium dc. dalam menghambat kanker rongga mulut - Syafiqa Amelia, Dinda; Sandra, Ferry; Ihsan Rizal, Muhammad (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background(s): Oral cancer is one of the most highly prevalent cancers with high mortality rate. Advanced-stage cancer often treated with chemotherapy. Chemotherapy does not differentiate between killing tumor cells and normal cells, leading to a range of side effects. Identifying effective approaches with minimal side effects for cancer treatment remains a significant priority within the medical field. Objective(s) : This review aimed to investigate potential avenues for future research on oral cancer using Z. acanthopodium Method(s) : References for this article were determined through searches of PubMed, Google Scholar, and official websites of global health organizations. The search terms were “cancer”, “oral cancer”, “anticancer”, “Zanthoxylum acanthopodium”, “apoptosis” from 2014 to 2024. Main finding(s) : Phytochemical compounds found in plants have a significant role in cancer therapies. Z. acanthopodium fruit has been used in anticancer research due to its wide array of bioactive compounds. Previous studies have shown the anticancer properties of Z. acanthopodium DC. against blood and breast cancer cell lines. Research on its anticancer activity against oral cancer has never been reported. Conclusion(s) : Recent findings confirm Z. acanthopodium as a rich source of bioactive compounds with potential anticancer properties. Further research on its anticancer activity against oral cancer should be promoted.